FACTORS ASSOCIATED WITH VISUAL INSPECTION OF ACETIC ACID (IVA) IN FERTIL AGE WOMEN IN PANGKE BARAT VILLAGE, MERAL BARAT DISTRICT - Nofuz, Mazidatun; Harahap, Juraida Roito; Sartika, Yan (Poltekkes Kemenkes Riau Under Health Ministry Republik Indonesia, 2021)
The incidence of cervical cancer is 85 % in developing countries. IVA is one of the early detection methods to discover abnormalities in the cervix. This study aims to determine the relationship between age, parity, education, occupation, family history of cancer and exposure to information on IVA examinations in Pangke Barat Village, Karimun Regency in Januari – May 2021. This type of study was cross sectional with female population from PUS recorded in the register Posyandu Dahlia Pangke Barat Village as many as 176 people. Sampling by simple random sampling. Data were analyzed using chi-square test. There is no relationship between age, parity, family history of cancer and information exposure to IVA examination. There is relationship between education ( p=0.01) and work ( p=0.00 ). Women with low education did not IVA check 4.516 time, and women who did not work 8.314 times did not IVA check. It is suggested to the Meral Barat Public Helath Center to futher improve health promotion using more attractive promotional media.